Creating Color Image Signature Based On Laplacian Equation - Jamil Al-Azzeh; Bilal Zahran; Ziad Alqadi; Belal Ayyoub; Muhammed Mesleh (JOIV : International Journal on Informatics Visualization, 2019)
Colour image retrieval, identification and recognition play an important role in vital computerized applications, so creating an image signature which can be used as a key to identify the image is an essential and important problem to be solved.Â In this paper a new method of image signature extraction will be proposed. The proposed method will be implemented and tested and the experimental results will be compared with other method results to prove the efficiency of the proposed method by mean of creating a unique signature which will require a minimum memory space and a smaller time to extract the signature.